Theological perspectives on accounting - McPhail, Ken; Garringe, Tim; Gray, Rob (Accounting, auditing & accountability journal, 2004)
This paper explores the issue of accounting and accountability in the spirituality and practices of an ecumenical Christian group - the Iona Community. Fundamental to the existence and operation of the Iona Community is their Rule, which requires all full-members to account to each other for their use of money and time. This paper explores the development of that Rule and how it is actualised. It examines the accounting practices of individuals in the Community and the distinction between individualising and socialising accountabilities. Findings reported challenge the assumption that accounti.